Pengembangan LKPD Berbasis Pendekatan Saintifik pada Tema Sumber Daya Alam di Kelas IV Sekolah Dasar : Penelitian - Siti Nurjannah Munthe; Beta Rapita Silalahi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the feasibility of LKPD Media on the theme of natural resources in Grade IV Elementary School. This study is a development research (Research and Development) using the ADDIE development model which includes five stages, namely Analysis, Design, Development, Implementation, and Evaluation. However, this study only goes up to three stages, namely only up to the Development stage. The instrument used to collect data is a questionnaire. The data analysis technique used is a qualitative descriptive analysis technique. From the validation results with a language expert validator, a score of 80 was obtained with the criteria of